2014
DOI: 10.1371/journal.pone.0111123
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Erosion and Eating Disorders: A Systematic Review and Meta-Analysis

Abstract: BackgroundEating disorders are associated with the highest rates of morbidity and mortality of any mental disorders among adolescents. The failure to recognize their early signs can compromise a patient's recovery and long-term prognosis. Tooth erosion has been reported as an oral manifestation that might help in the early detection of eating disorders.ObjectivesThe aim of this systematic review and meta-analysis was to search for scientific evidence regarding the following clinical question: Do eating disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 30 publications
2
76
1
7
Order By: Relevance
“…The adapted version of the NOS can be found in Supporting Information, . Studies above the median score (7/7 and 8/8) were the cut‐off point for articles of high quality …”
Section: Methodsmentioning
confidence: 99%
“…The adapted version of the NOS can be found in Supporting Information, . Studies above the median score (7/7 and 8/8) were the cut‐off point for articles of high quality …”
Section: Methodsmentioning
confidence: 99%
“…We assessed risk of bias using the Newcastle-Ottawa Scale (NOS) for cross-sectional and cohort studies [13, 14]. The NOS is a tool to assess bias in studies where each bias-reducing criterion is used to award stars: selection of participants (maximum of four stars for cohort and five for cross-sectional), comparability of groups (maximum of two stars), and measurement (maximum of three stars).…”
Section: Methodsmentioning
confidence: 99%
“…This occurs in patients with bulimia, regurgitation, rumination, and gastroesophageal reflux disease . Recently, it was reported that patients with eating disorders had more risk of erosion (OR = 12.4), which is increased when vomiting is self-induced (OR = 19.6) [Hermont et al, 2014]. In addition, around 10-20% of the population suffer from gastroesophageal reflux disease [Dent et al, 2005].…”
Section: Introductionmentioning
confidence: 99%